Effect of projection variables on throw distance and flight time in an american football throw - Linthorne, N. P.; Modebe, A.-S. N. (ISBS Proceedings Archive (Michigan), 2017)
In American football the ball is usually thrown to the receiver with near-maximum speed and a low angle so as to minimize the flight time. In this study a player performed maximum-effort throws using a wide range of projection angles. The throws were recorded by a video camera and a 2D biomechanical analysis was conducted to obtain mathematical expressions for the relationships between the projection variables. These expressions were then inserted into a model of the aerodynamic flight of an American football, and the throw distance and flight time were calculated. We that found the relationships between the projection variables had only a small effect on the projection angle and flight time for a pass to a receiver at a given distance. Players probably get the projection angle in a throw very nearly right through trial-and-error practice.